Analisis Perbandingan Material S45C Dan JSC270C Pada Proses Gas Soft Nitriding Dan Isonite Terhadap Surface Hardness, Compound Layer, Distribution Layer, Dan Struktur Mikro - Marshanda, Deviana Dewi; Prabowo , Imam; Theresia , Thia (Journal of Metallurgical Engineering and Processing Technology, 2025)
This research investigates the comparative effects of Gas Soft Nitriding (GSN) and Isonite surface treatment processes on two types of steel materials: S45C and JSC270C. Conducted at PT Parker Metal Treatment Indonesia, the study aims to analyze how these treatments influence surface hardness, compound layers, diffusion layers, and microstructure. A series of laboratory and field experiments were carried out, including micro-Vickers hardness testing and optical microscopy, to evaluate the mechanical enhancements and structural changes post-treatment. Results indicate that Gas Soft Nitriding generally produces a thicker compound layer and higher surface hardness compared to Isonite. However, the effectiveness of each process depends significantly on the material type and specific treatment parameters. These findings provide practical insight for industrial applications seeking to enhance wear resistance and surface performance of steel components through optimized thermochemical processes.